Snow country - Kawabata, Yasunari 1899-1972; Seidensticker, Edward 1921-2007 (New York Vintage Books, 1996)
With the brushstroke suggestiveness and astonishing grasp of motive that won him the Nobel Prize for Literature, Yasunari Kawabata tells a story of wasted love set amid the desolate beauty of western Japan, the snowiest region on earth. It is there, at an isolated mountain hotspring, that the wealthy sophisticate Shimamura meets the geisha Komako, who gives herself to him without regrets, knowing that their passion cannot last. Shimamura is a dilettante of the feelings; Komako has staked her life on them. Their affair can have only one outcome. Yet, in chronicling its doomed course, one of Japan's greatest modern writers creates a novel dense in implication and exalting in its sadness.
Originally published in Japan in hardcover as Yukiguni.
"Winner of the Nobel prize for Literature."--Cover.
Keywords: Romance fiction